The good dinosaur - Sohn, Peter; LeFauve, Meg; Benson, Erik (Screenwriter); Mann, Kelsey; Peterson, Bob, 1961-; Ream, Denise; Lasseter, John; Unkrich, Lee; Stanton, Andrew; Wright, Jeffrey; McDormand, Frances; Ochoa, Raymond, 2001-; et al. (Burbank, CA : Buena Vista Home Entertainment, 2016)
What if the asteroid that forever changed life on Earth missed and giant dinosaurs never became extinct? In this epic journey into the world of dinosaurs, an Apatosaurus named Arlo makes an unlikely human friend. While traveling through a harsh and mysterious landscape, Arlo learns the power of confronting his fears and discovers what he is truly capable of.
DVD, NTSC region 1, widescreen (2.39:1) presentation; Dolby Digital 5.1 surround, Dolby Digital 2.0.
English, dubbed French, or dubbed Spanish dialogue; optional English, French and Spanish subtitles; English subtitles for the deaf and hard-of-hearing (SDH); closed-captioned; English descriptive audio track for people with visual impairments.
Voices of: Jeffrey Wright, Frances McDormand, Raymond Ochoa, Sam Elliott, A.J. Buckley, Anna Paquin.
Music, Mychael Danna, Jeff Danna ; executive producers John Lasseter, Lee Unkrich, Andrew Stanton
Originally released as a motion picture in 2015.
Widescreen (2.39:1).
Keywords: Dinosaurs -- Juvenile films; Fear -- Juvenile films; Courage -- Juvenile films; Dinosaurs; DVD-Video discs; Fear; Animated films; Children's films; Feature films; Fiction films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Animated films; Children's films; Feature films; Juvenile works; Motion pictures